2016
DOI: 10.1002/polb.24013
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous morphological stability and high charge carrier mobilities in donor-acceptor block copolymer/PCBM blends

Abstract: Donor-acceptor block copolymers (BCP), incorporating poly(3-hexylthiophene) (P3HT), and a polystyrene copolymer with pendant fullerenes (PPCBM) provide desired stable nanostructures, but mostly do not exhibit balanced charge carrier mobilities. This work presents an elegant approach to match hole and electron transport in BCP by blending with molecular PCBM without causing any macrophase separation. An insufficient electron mobility of PPCBM can be widely compensated by adding PCBM which is monitored by the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…This result implies that the diffusion of PCBM molecules into the perovskite layer is crucial to the elimination of hysteresis in PSCs, consistent with the requirement of thermal annealing to passivate the defects and decrease the trap density in the perovskite layer. [ 20 ] Here, we note that, the relatively poorer performance of the device with PPCBM is probably caused by its relatively lower electron mobility, [ 26 ] hindering the effective electron extraction by TiO 2 /FTO layer.…”
Section: Resultsmentioning
confidence: 99%
“…This result implies that the diffusion of PCBM molecules into the perovskite layer is crucial to the elimination of hysteresis in PSCs, consistent with the requirement of thermal annealing to passivate the defects and decrease the trap density in the perovskite layer. [ 20 ] Here, we note that, the relatively poorer performance of the device with PPCBM is probably caused by its relatively lower electron mobility, [ 26 ] hindering the effective electron extraction by TiO 2 /FTO layer.…”
Section: Resultsmentioning
confidence: 99%
“…The rigidity of the fibers prevents penetration of the NDI-C9 molecules into the P3HT ''phase'' and leads to a distinct phase separation to facilitate the charge transport. 42,43 For this reason, the ambipolar mobilities in these nano-structured bulk-like heterojunction structures were higher in comparison to the planar bilayer heterojunction films obtained solely from solution. In our previous work we reported that hole and electron mobilities were increased by one order of magnitude when P3HT fibrils were surrounded by a PCBM phase.…”
Section: Bilayer Film Structurementioning
confidence: 95%
“…Despite its importance, the glass transition of many organic semiconductors is not easily determined. The change in heat capacity in the vicinity of T g for organic semiconductors is often too weak to detect by DSC. , Other techniques, such as dynamic mechanical analysis (DMA) or variable-temperature ellipsometry (which has been applied to polyolefins , as well as conjugated polymers), are often required. The glass transition can also be predicted computationally, as atomistic and coarse-grained molecular dynamics (MD) simulations have been used to obtain values that are in good agreement with experiment …”
Section: Thermal and Mechanical Properties And How To Measure Themmentioning
confidence: 99%